Comparisons of Stroke Knowledge and Health Behaviors in Patients With Hypertensive Stroke at Different Recurrence Risk Strata: The Comprehensive Reminder System Based on the Health Belief Model Study. Issue 2 (March 2022) - Li, Jing-Jing; Tan, Ju-Xiang; Zhu, Fen-Yan; Wu, Zhen; Ruan, Heng-Fang; Li, Zhuo-Ran; Wan, Li-Hong
Abstract : Background: Risk factor management via behavioral change contributes substantially to secondary stroke prevention. The health belief model identified self-perceived risk as a significant factor in behavior change. In previous studies, people have tended to incorrectly estimate their risk of stroke. Little is known about the differences in stroke knowledge and health behaviors in patients who have had a stroke with different risks of stroke recurrence in China. Objective: The aims of this study were to determine the accuracy of self-perceived risk of stroke recurrence and to compare stroke knowledge and health behaviors in patients with hypertensive stroke at different recurrence risk strata. Methods: Baseline data from 174 patients in the Comprehensive Reminder System based on the Health Belief Model (CRS-HBM) study were used. Self-perceived risk was assessed via the susceptibility subcategory of the Short-Form Health Belief Model Scale, and actual risk was stratified using the Essen Stroke Risk Score. Results: Only 27.0% of the patients estimated their risks of stroke recurrence accurately. Patients who perceived themselves to be at higher risk had better knowledge of warning signs. Compared with patients who underestimated their risk of stroke recurrence, those who accurately estimated or overestimated their risk less likely to smoke. Conclusions: Most patients incorrectly estimated their risk of stroke recurrence. Communicating with patients about their future risk of recurrent stroke may help improve their stroke knowledge and health behaviors. Implementation of the Comprehensive Reminder System based on the Health Belief Model focusing on risk education aimed at prevention of stroke recurrence is warranted in China.